UK police custody officers’ psychosocial hazard exposures and burnout - Houdmont, Jonathan (Emerald, 2013)
Purpose – Stress research in the UK policing has largely neglected to account for variance in the type of psychosocial hazard officers are exposed to across policing roles, highlighting the need for role-specific research that is capable of informing similarly specific stress reduction interventions. This study aimed to develop and assess exposure to a taxonomy of psychosocial hazards specific to the UK police custody work, consider the burnout profile of custody officers, explore relations between psychosocial hazard exposure and burnout, and compare the exposures of burned out and non-burned out custody officers.